Investigation of the abrasive durability of the multilayer diamond-like coatings for the ring-shaped dry gaseous seals made of SiC - Vasyliev, V.V.; Luchaninov, A.A.; Strel’nitskij, V.E. (Вопросы атомной науки и техники, 2019)
The abrasion resistance of multi-layer vacuum-arc diamond-like (DLC) coatings of various architectures: quasigradient, as well as coatings with alternating hard and soft layers, whose structure and mechanical characteristics are specified by the amplitude of the bias potential and the deposition time of each layer are investigated. Increasing the thickness of the DLC to 6…7 μm by using a multilayer architecture with alternating soft and hard layers allows to improve the abrasion resistance of the protective coating, however, the adhesion of such coatings on silicon carbide is somewhat lower than that of the quasigradient ones. The parameters of the process of synthesis of DLCs, provid-ing a significant improvement in the mechanical characteristics of multilayer coatings, in comparison with the sin-gle-layer ones, are established. Досліджено абразивну стійкість багатошарових вакуумно-дугових алмазоподібних покриттів (АПП) різної архітектури: квазіградiєнтних, а також покриттів з періодично повторюваними твердими та м’якими шарами, структура та механічні характеристики яких задаються амплітудою потенціалу зміщення і тривалістю осадження кожного шару. Збільшення товщини АПП до 6…7 мкм за рахунок використання багатошарової архітектури з періодично повторюваними твердими та м’якими шарами дозволяє покращити абразивну стійкість захисного покриття, однак адгезія таких покриттів на карбіді кремнию дещо нижча, ніж у квазіградієнтних. Встановлено параметри процесу синтезу АПП, які забезпечують суттєве поліпшення механічних характеристик багатошарових покриттів порівняно з одношаровими. Исследована абразивная стойкость многослойных вакуумно-дуговых алмазоподобных покрытий (АПП) различной архитектуры: квазиградиентных, а также покрытий с чередующимися твердыми и мягкими слоями, структура и механические характеристики которых задаются амплитудой потенциала смещения и временем осаждения каждого слоя. Увеличение толщины АПП до 6…7 мкм за счет использования многослойной архитектуры с чередующимися мягкими и твердыми слоями позволяет улучшить абразивную стойкость защитного покрытия, однако адгезия таких покрытий на карбиде кремния несколько ниже, чем у квазиградиентных. Установлены параметры процесса синтеза АПП, обеспечивающие существенное улучшение механических характеристик многослойных покрытий по сравнению с однослойными.